Contrasting Magnetic Behaviors in Rhodium‐ and Ruthenium‐Doped Cubic Perovskite SrFeO3: Nearly Ferromagnetic Metal versus Spin‐Glass Insulator. Issue 49 (2nd November 2016) - Kinoshita, Masataka; Sakai, Hideaki; Hayashi, Naoaki; Tokura, Yoshinori; Takano, Mikio; Ishiwata, Shintaro
Abstract: The effects of Rh and Ru doping for SrFeO3, a helimagnetic metal with a cubic perovskite structure, are studied by magnetic and resistivity measurements. Although SrRhO3 is a paramagnetic metal and SrRuO3 is a ferromagnetic one, the Rh doping induces a nearly ferromagnetic metallic state, whereas the Ru doping induces a spin‐glass insulating state. Mössbauer measurements evidence a marked difference between SrFe0.8 Rh0.2 O3 and SrFe0.8 Ru0.2 O3 in the formal valences of Fe, which are estimated to be 4+ and 3.75+, respectively. The contrasting magnetic behaviors of Rh‐ and Ru‐doped SrFeO3 are discussed in terms of the subtle balance between the double‐exchange ferromagnetism and the superexchange antiferromagnetism. Abstract : Doping control : The cubic perovskites SrFe1− x Rh x O3 (0≤ x ≤0.3) and SrFe1− y Ru y O3 (0≤ y ≤0.5) are synthesized by a high‐pressure technique. The former with x above 0.1 shows nearly metallic and ferromagnetic behavior, whereas the latter with y above 0.1 shows insulating and spin‐glass behavior. The contrasting behaviors can be ascribed to the difference in the valence of Fe, which modifies the competing magnetic interactions in helimagnetic SrFeO3 .